An alternative route to single ion conductivity using multi-ionic salts. Issue 3 (6th March 2018) - Chereddy, Sumanth; Chinnam, Parameswara Rao; Chatare, Vijay; diLuzio, Stephen Patrick; Gobet, Mallory P.; Greenbaum, Steven G.; Wunder, Stephanie L.
Abstract : Polyoligomeric silsesquioxanes with eight (LiNSO2 CF3 ) groups can be dissolved at very high loadings into tetraglyme, forming solvent-in-salt electrolytes, and stable colloids with increasing amount of tetraglyme. Li + ions can migrate by diffusive or coordinated hopping motions. High t Li + and conductivities are obtained. Abstract : Multi-ionic lithium salts comprised of polyoligomeric silsesquioxanes (POSS) functionalized with eight – (LiNSO2 CF3 ) groups, referred to as POSS-(LiNSO2 CF3 )8, can be dissolved at very high loadings into tetraglyme (G4 ), where they can be considered solvent-in-salt electrolytes. With increasing dilution, colloidal solutions are formed. Two systems were investigated, neat POSS-(LiNSO2 CF3 )8 in G4 and mixtures of POSS-(LiNSO2 CF3 )8 with LiPF6 or lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). PFG-NMR indicates that Li can be un-dissociated, completely dissociated and surrounded by G4 molecules, or as contact ion pairs (in which there are 3–4 ether oxygen contacts and one contact with the oxygen from the anion). Equilibria exist between the species of POSS-(LiNSO2 CF3 )8 and if there is rapid equilibration between the Li states, and close enough proximity between the POSS-(LiNSO2 CF3 ), then the Li + ions can migrate by a Grotthus-type coordinated hopping mechanism, as well as by a purely diffusive motion. Unlike polymer single ion conductors, where the backbone flexibility permits cluster/aggregate formation, which inhibits escape and mobility of the Li + ions, the rigid POSS cube and its colloidal structure in G4 prevents formation of POSS-(NSO2 CF3 − )⋯Li + ⋯( − CF3 NSO2 )-POSS triplets. Instead, the solvated Li + in POSS-(NSO2 CF3 − )⋯Li + ⋯G4 can be more easily removed to form conductive G4 ⋯Li +− ⋯G4 . Good ionic conductivities (∼10 −4 S cm −1 ) and lithium ion transference numbers of t PP+ = 0.65 can be achieved in these systems. Mixtures of 80 wt% LiTFSI and 20 wt% POSS-(LiNSO2 CF3 )8 in G4 at an O/Li ratio of 20/1, yield both high conductivity ( σ = 3.3 × 10 −3 S cm −1 ) and high ( t PP+ = 0.65) transference number. Stable cycling between C/2 and 2C with high capacity retention was achieved using Li/[G4 /80 wt% LiTFSI/20 wt% POSS-(LiNSO2 CF3 )8 ]/LiFePO4 half-cells.